The Milky Way disk non‐axisymmetries and galactoseismology. Issue 8 (30th September 2016) - Famaey, B.; Monari, G.; Siebert, A.
Abstract: Current Galactic dynamical models still most often rely on the assumptions of a smooth time‐independent and axisymmetric gravitational potential. On the other hand, ab initio simulations in a cosmological context are not very flexible to precisely produce a model of our own Galaxy, or to disentangle the internal and the external/environmental effects on its evolution. To make such a disentanglement possible, one can first try to isolate all the possible effects of one main nonaxisymmetric perturber, such as the bar or the spiral arms, through perturbation theory applied to smooth time‐independent axisymmetric potentials. For instance, it has recently been realized in this way that observed vertical oscillations of the Galactic disk could be due to such internal perturbations, rather than to external perturbers as previously believed. Here we summarize the general analytical framework, in the context of perturbation theory, which allowed us to compute the stellar vertical bulk motions generated by a single internal perturber such as the Galactic bar. We point out that non‐linear couplings can nevertheless be present when multiple non‐axisymmetric perturbers – such as multiple spiral patterns together with a central bar – are present simultaneously, thus potentially enhancing the effect presented here.